2018
DOI: 10.1177/0888406418801913
|View full text |Cite
|
Sign up to set email alerts
|

Using Multimedia Instruction and Performance Feedback to Improve Preservice Teachers’ Vocabulary Instruction

Abstract: High-quality, effective vocabulary instruction is essential for supporting all students’ academic success, and it is particularly important for students with disabilities. Teacher preparation programs are faced with the challenge of not only training preservice teachers to provide effective vocabulary instruction across grades and content areas, but also to prepare them to teach students with disabilities. This randomized control trial included 200 preservice teachers. We tested the effects that a combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 40 publications
(58 reference statements)
1
20
0
1
Order By: Relevance
“…Future research in this area should examine whether watching a CAP-T improves preservice teachers’ implementation of FBA practices. In a recent study, Peeples et al (2018) evaluated whether multimedia plus performance feedback improved participants application of practices related to vocabulary instruction. Researchers could explore topics such as identifying the function of behavior and matching the intervention to behavioral function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future research in this area should examine whether watching a CAP-T improves preservice teachers’ implementation of FBA practices. In a recent study, Peeples et al (2018) evaluated whether multimedia plus performance feedback improved participants application of practices related to vocabulary instruction. Researchers could explore topics such as identifying the function of behavior and matching the intervention to behavioral function.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, CAP-Ts were designated as an evidence-based practice for improving preservice teachers’ knowledge and learning (Dieker et al, 2014). To date, there are 15 published CAP-T randomized controlled trials with significant effects aimed at improving preservice teachers’ knowledge about topics such as phonological awareness (Kennedy et al, 2013), curriculum-based measures (Kennedy et al, 2015), vocabulary instruction (Peeples et al, 2018), positive behavior supports (Kennedy et al, 2011), and FBAs (Hirsch et al, 2015; Kennedy et al, 2016). Kennedy et al (2016) served as a pilot study for the current research.…”
Section: Empirical Support For Cap-tsmentioning
confidence: 99%
“…However, unlike classroom experiences later on in their teacher preparation program (e.g., student teaching), the majority of these experiential experiences linked to courses may not have direct university supervisors, but instead, rely more on the support of the cooperating teacher. Therefore, it is up to the course faculty to systematically integrate cycles of practice and feedback into their courses, since research shows that frequent opportunities to practice and receive feedback can improve the efficiency with which preservice teachers acquire and implement practices accurately (Peeples et al, 2018;Sayeski et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A social validity questionnaire, however, showed that the teachers were positive about the intervention. More recently, Peeples et al (2018) compared the same methods created for the Kennedy et al (2017) study to a lecture condition and a condition where teachers simply read an article. All 200 teachers received written feedback after observations, but the podcast group received performance feedback based on the Kennedy observation system.…”
Section: Research On Using Technology For Professional Developmentmentioning
confidence: 99%
“…More recently, Peeples et al. (2018) compared the same methods created for the Kennedy et al. (2017) study to a lecture condition and a condition where teachers simply read an article.…”
Section: Research On Using Technology For Professional Developmentmentioning
confidence: 99%